2018
DOI: 10.1042/cs20171625
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor prolyl hydroxylase inhibitor roxadustat (FG-4592) protects against cisplatin-induced acute kidney injury

Abstract: Renal hypoxia occurs in acute kidney injury (AKI) of various etiologies. Activation of hypoxia-inducible transcription factor (HIF) has been identified as an important mechanism of cellular adaptation to low oxygen. Preconditional HIF activation protects against AKI, suggesting a new approach in AKI treatment. HIF is degraded under normoxic conditions mediated by oxygen-dependent hydroxylation of specific prolyl residues of the regulative α-subunits by HIF prolyl hydroxylases (PHD). FG-4592 is a novel, orally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 43 publications
4
97
0
Order By: Relevance
“…These studies support a protective role of FoxO3 during the AKI-to-CKD transition by reducing oxidative stress and increasing autophagy. The protective role of prolyl hydroxylation inhibition was also demonstrated in a study showing that the prolyl hydroxylase inhibitor roxadustat (FG-4592) afforded protection against cisplatin nephrotoxicity [191].…”
Section: Foxo3-mediated Autophagy Induction and Kidney Diseasementioning
confidence: 86%
See 1 more Smart Citation
“…These studies support a protective role of FoxO3 during the AKI-to-CKD transition by reducing oxidative stress and increasing autophagy. The protective role of prolyl hydroxylation inhibition was also demonstrated in a study showing that the prolyl hydroxylase inhibitor roxadustat (FG-4592) afforded protection against cisplatin nephrotoxicity [191].…”
Section: Foxo3-mediated Autophagy Induction and Kidney Diseasementioning
confidence: 86%
“…↑ autophagy [191] Aristolochic acid (AA)-induced nephropathy AA exposure ↑ autophagy with ↑ ERK1/2 activity [192] UUO FoxO3 ↑ autophagy through nuclear expression of Atg proteins [193] Prolonged IR (AKI to CKD transition) FoxO3 ↑ autophagy [194] Ischemic preconditioning Increased FoxO3 by overexpression of SGK1 ↑ autophagy [196] Podocyte injury Aldosterone ↑ autophagy through FoxO1-Rab7 [195] STZ-induced DN FoxO1 overexpression ↑ autophagy [196] Podocyte injury Atrasentan ↑ autophagy by increased expression of FoxO1 by downregulating miR21 [197] 4.2.9. GCN2 Kinase-Mediated Autophagy Induction and Kidney Disease Another kinase, known as general control nonderepressible 2 (GCN2), is activated in response to deprivation of amino acids and induces autophagy [199].…”
Section: Model/ Kidney Disease Agent/drug Effect On Autophagy Referencementioning
confidence: 99%
“…Serum levels of IL-6 and TNF-α were measured by ELISA kits (Dakewe Biotech, Beijing, China) in accordance with the manufacturer's instructions. The levels of Cystatin C in the serum were also determined by a mouse Cystatin C ELISA kit ( E -EL-M0389C, Elascience, China) [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported in the literature that the incidence of AKI after APAP overdose is 2%~10% (Reshi et al, ). KIM‐1, NGAL, and Cys‐C are considered to be reliable renal biomarkers, which are normally not expressed in normal kidney tissues, but are highly expressed when they are damaged by kidney toxicity or ischemia (Soetikno et al, ; Yang, et al, ). Therefore, our results indicate that SDAPR retains HK‐2 cells in APAP‐induced nephrotoxicity to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…(Sui, Zhang, Huo, & Zhang, ). According to reports, sika deer antler protein (SDAPR) can protect cisplatin‐induced and gentamicin‐induced AKI (Sun et al, ; Yang et al, ). The study also showed that antlers can resist LPS‐induced acute lung injury by activating AMPK/Nrf2 pathway (Chang et al, ).…”
Section: Introductionmentioning
confidence: 99%